Molecular monitoring of chronic myeloid leukemia: principles and interlaboratory standardization - Cross, Nicholas C. P.; Hochhaus, Andreas; Müller, Martin Christian (Annals of hematology, 2015)
Serial quantification of BCR-ABL1 messenger RNA (mRNA) is an important therapeutic indicator for patients with chronic myeloid leukemia, but historically, there has been substantial variation in results reported by different laboratories. To help improve the comparability of results, an international scale (IS) for BCR-ABL1 was proposed which is being implemented by testing laboratories worldwide. This is being achieved most commonly by the derivation of laboratory-specific conversion factors, but increasingly by the use of kits or reagents that are calibrated to the first World Health Organization International Genetic Reference Panel for quantitation of BCR-ABL1 mRNA. Recent attention has focused on the need to define and validate levels of deeper molecular response (MR) within the context of the IS. While there has been substantial progress in the alignment of results, BCR-ABL1 measurement is technically challenging and standardization is an ongoing process.